Copernicus Sentinel and Landsat data work together to support archaeological research - Agapiou, Athos (My University, 2020)
A team of researchers in Cyprus have been studying how to use Copernicus Sentinel and Landsat data together, to improve the domain of remote sensing archaeology. Nowadays, a variety of satellite images have become accessible to researchers, while big data cloud platforms allow them to deal with a vast number of datasets. Earth Observation sensors continually provide images with different spectral and spatial characteristics. However, there is still difficulty related to these sensors meeting specific needs and challenges such as those of cultural heritage, and supporting archaeological research world-wide. The fusion and synergistic use of different sensors can be exploited to maximise the impact of Earth Observation sensors, thus enhancing their benefit to the scientific community. Monitoring archaeological sites and monuments over large areas, including not only standing but also heritage remains well hidden under the ground's surface, is of great importance towards their preservation and protection against natural and man-made hazards. Observations from satellites can be used to detect buried, and still unknown archaeological remains, therefore providing additional insight to archaeologists studying an area, revealing lost landscapes that have been dramatically changed by modern development. Detection of archaeological remains by satellites can be achieved through the study of spectral anomalies of soil or vegetation, which can be linked to the presence of subsurface archaeological remains. Archaeological proxies, such as soil and crop marks, can be depicted from multispectral datasets due to their different spectral signature in comparison to the surrounding area.
Keywords: Copernicus Sentinel; Landsat data; Remote sensing archaeology